Pengaruh Mutu Pelayanan terhadap Tingkat Kepuasan Pasien Rawat Inap di Puskesmas Lapai Kabupaten Kolaka Utara - Lisna; Muhammad Syafar; Muhammad Rifai (2022)
Public services in the health sector can be carried out in hospitals and health centers throughout Indonesia. Community Health Center is a service facility that organizes public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest public health degree in its working area. The purpose of the study was to influence service quality on the level of satisfaction of inpatients at the Lasusua Public Health Center, North Kolaka Regency in 2021. The type of research used was an analytical survey research with a